2014
DOI: 10.1007/s11934-014-0461-y
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Incontinence: What Takes Precedence in Its Management?

Abstract: Mixed urinary incontinence is a commonly encountered condition for urologists, urogynecologists, and primary care providers. In this review, we discuss the approach to the evaluation and management of patients with simultaneous stress and urgency urinary incontinence. The available evidence for treatment modalities in the setting of mixed urinary incontinence is presented, and we discuss our treatment algorithm for this common but challenging clinical scenario. An accurate assessment of stress and urge symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…However, because beta-3 agonists are effective for OAB, it is inferred that they would exhibit the same effectiveness as anticholinergics for mixed urinary incontinence. 56 Further evidence needs to be gathered going forward (Level 5; recommendation Grade C).…”
Section: Cq14 Do Therapeutic Drugs For Oab Affect Cognitive Function?mentioning
confidence: 99%
“…However, because beta-3 agonists are effective for OAB, it is inferred that they would exhibit the same effectiveness as anticholinergics for mixed urinary incontinence. 56 Further evidence needs to be gathered going forward (Level 5; recommendation Grade C).…”
Section: Cq14 Do Therapeutic Drugs For Oab Affect Cognitive Function?mentioning
confidence: 99%
“…While an attempt was made to conduct a randomized clinical trial evaluating initial OAB therapy or surgical therapy, the trial failed to recruit patients, so there is no high-level evidence supporting this approach. 2 However, secondary analysis of pooled, randomized, placebo-controlled trials for OAB have demonstrated that a significant proportion of women with urge predominant mixed urinary incontinence have complete resolution of their incontinence. 19 This suggests that either these patients were incorrectly classified as mixed incontinence (despite the rigorous assessment that goes along with a clinical trial), or that the etiology of the stress incontinence component of some women's mixed symptoms responds to anticholinergic therapy (for example, the case of stress induced DO).…”
Section: Non-surgical Treatmentmentioning
confidence: 99%
“…20 Other medical options include the off-label use of imipramine (a tricyclic antidepressant) or duloxetine (a serotonin and norepinephrine reuptake inhibitor). 2 Likely the results of anticholinergic therapy in this population can be applied to beta-3 agonists.…”
Section: Non-surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…If the UUI component is equally as bothersome as the SUI component (as reported by the patient in our scenario), primary treatment of UUI symptoms has been recommended. 15 There is good evidence supporting the use of medications in the first instance; for example, the anticholinergic drugs solifenacin, 16 tolterodine 17 and transdermal oxybutynin, 18 as well as the recently introduced beta3 agonist mirabegron, 19 are all known to be safe, effective and well-tolerated in patients with MUI. When medical therapy is ineffective, intravesicular injection of onabotulinumtoxinA is safe, significantly improves symptoms for 6–12 months and can be repeated.…”
Section: Should the Urge Urinary Incontinence Be Treated First?mentioning
confidence: 99%